Capacity building for school development: current problems and future challenges. Issue 5 (19th October 2016) - Ho, Dora; Lee, Moosung
ABSTRACT: This article offers a theoretical discussion on the current problems and future challenges of school capacity building in early childhood education (ECE), aiming to highlight some key areas for future research. In recent years, there has been a notable policy shift from monitoring quality through inspection to improving quality through school capacity building in early childhood institutions in the global discourse for quality. Reflecting this policy shift and its implications on school development, ECE in Hong Kong is used as an illustrative example to deliberate the issues of school capacity building in Chinese educational contexts. We identify three challenging contexts: (1) low professional qualification and minimal teacher education resulting in a deficit approach to processional development, (2) absence of school-based professional learning culture for empowering teachers as internal agents of change, and (3) hierarchical culture within a school and between university and school hindering the process of school capacity building. Corresponding to these challenges, we aim to propose two suggestions, including (1) empowering teachers in ECE through school-based professional learning community and (2) promoting authentic external support in the process of university–school collaboration. Finally, we further propose specific directions for future research on school capacity building in ECE in Hong Kong. In doing so, it will contribute to knowledge-based development in school capacity building in Chinese educational contexts.